Pengaruh Beban Kerja, Lingkungan Kerja dan Semangat Kerja terhadap Kinerja Karyawan Cv Istiqomah Furniture Klaten - Erinna Dian Rahmayanti; Asih Handayani (Jurnal Publikasi Ilmu Manajemen, 2025)
This study aims to analyze the influence of workload, work environment, and work enthusiasm on employee performance at CV Istiqomah Furniture Klaten. There is evidence of a decline in employee performance, suspected to be related to these factors, which constitutes the main problem underlying this research. The entire population, consisting of 35 employees, was used as the sample in this quantitative study. Multiple linear regression analysis was employed to analyze data collected through questionnaires. The results indicate that work enthusiasm has a greater impact on employee performance than workload and work environment. The findings highlight the importance of non-physical components such as motivation and enthusiasm in enhancing productivity. The practical implication of this study is the necessity for the company to focus on boosting work enthusiasm through motivational and appreciation programs, rather than solely concentrating on workload management or physical improvement of the work environment. The study highlights the importance of non-physical components, such as motivation and enthusiasm, in improving employee performance. While a well-designed work environment and manageable workload are important, they are not as significant as fostering a work culture that encourages enthusiasm, recognition, and appreciation. The practical implication of these findings is that the company should focus more on boosting work enthusiasm by implementing motivational programs, offering appreciation for achievements, and cultivating a positive organizational culture.